1990
DOI: 10.1128/jb.172.2.845-852.1990
|View full text |Cite
|
Sign up to set email alerts
|

Structure of macroamphiphiles from several Bifidobacterium strains

Abstract: Lipoteichoic acid-like substances, macroamphiphiles, were isolated from cell homogenates ofBifidobacterium bifidum YIT 4007 and YIT 4013, Bifidobacterium breve YIT 4010 and YIT 4014, and Bfidobacterium longum YIT 4021 by phenol extraction followed by nuclease digestion, gel chromatography, ion-exchange chromatography, and hydrophobic interaction chromatography. The macroamphiphile preparations from these five strains contained D-glucose, D-galactose, glycerol, phosphorus, L-alanine, and fatty acids in molar ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…Antigenic cross-reactivities suggested that similar lipoglycans were present in other bifidobacteria, since extracts from seven of eight bifidobacterial serological groups cross-reacted with antisera to the B. bifidum antigen (49). Lipoglycans with essentially the same structure as that proposed by Fischer (16) have been confirmed to be present in Bifidobacterium breve and Bifidobacterium longum strains (30).…”
Section: Structure and Biosynthesissupporting
confidence: 57%
“…Antigenic cross-reactivities suggested that similar lipoglycans were present in other bifidobacteria, since extracts from seven of eight bifidobacterial serological groups cross-reacted with antisera to the B. bifidum antigen (49). Lipoglycans with essentially the same structure as that proposed by Fischer (16) have been confirmed to be present in Bifidobacterium breve and Bifidobacterium longum strains (30).…”
Section: Structure and Biosynthesissupporting
confidence: 57%
“…ELISA reactivity was clearly shown to be associated with bacterial lipoglycans containing a ␤-1,5-galactofuranosyl chain. Only a few bifidobacterial lipoglycans have been structurally analyzed, but also other bifidobacterial species seem to contain reactive residues in their cell wall (7,18,30). This specific epitope can be detected as a surface antigen, shown by the reactivity of the suspended cell pellet, but also as an exoantigen, shown by the reactivity of the cellfree supernatant of a liquid culture (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…These glycerophosphates are substituted with L-alanine residues. This basic structure is common to all bifidobacteria, but the numbers of polymers and repeating units vary among strains (216).…”
Section: Fig 6 O-antigen Lps Biosynthesis and Lps Assembly And Transpmentioning
confidence: 99%